Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.jpeds.2018.10.053
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Diabetes in Utero Is Associated with Earlier Pubertal Timing and Faster Pubertal Growth in the Offspring: The EPOCH Study

Abstract: Objective: To examine the associations of in utero exposure to maternal diabetes with surrogate measures of offspring pubertal timing (age at peak height velocity [APHV]) and speed of pubertal growth (peak height velocity [PHV]).Study design: Data from 77 exposed and 340 unexposed youth followed from age 2 to 19 years (51% non-Hispanic white, 50% females) were analyzed using the Exploring Perinatal Outcomes among Children study, a historical prospective cohort. Maternal diabetes status was collected from obste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 41 publications
0
36
0
Order By: Relevance
“…Adiposity and 'over-nutrition' can be considered predictors of pubertal timing and principal determinants for the initiation and maintenance of pubertal maturational events (32), hence, the association between maternal GDM and offspring pubertal timing could be mediated by offspring adiposity and pre-adolescence BMI. This is supported by the analysis by Hockett et al (26), in which the association between maternal GDM and age at PHV is attenuated by adjustment for offspring BMI z-score.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Adiposity and 'over-nutrition' can be considered predictors of pubertal timing and principal determinants for the initiation and maintenance of pubertal maturational events (32), hence, the association between maternal GDM and offspring pubertal timing could be mediated by offspring adiposity and pre-adolescence BMI. This is supported by the analysis by Hockett et al (26), in which the association between maternal GDM and age at PHV is attenuated by adjustment for offspring BMI z-score.…”
Section: Discussionmentioning
confidence: 55%
“…Of the remaining 248, were not relevant to the research question and were excluded on the basis of title and abstract, leaving 18 studies for full-text assessment. Eleven articles were excluded at this stage: four articles were conference proceedings, oral presentations or commentary articles (13)(14)(15)(16); two articles did not include any of the outcomes we were interested in (17,18); one article did not analyse GDM as a predictor for pubertal timing due to an insufficient number of subjects with GDM (19); two articles did not provide a comparator cohort (20,21); two articles only reported Tanner stage at baseline and did not consider age/timing of puberty (22,23). The seven remaining studies were included in the review (Fig.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…He concluded that height during puberty needs to be measured only annually and, with slightly lower precision, just four biennial measurements can be sufficient [7]. aPHV and PHV were modeled using the SITAR method and they found that median aPHV was reached approximately three months earlier in youth exposed to maternal diabetes compared with unexposed youth (p < 0.03) [15]. Youth exposed to maternal diabetes had a faster PHV than unexposed youth: exposed girls had a 10.5% greater median PHV compared with unexposed girls, and exposed boys had a 4.0% greater median PHV compared with unexposed boys (p < 0.001 for exposure by sex interaction) [15].…”
Section: Discussionmentioning
confidence: 99%
“…Pubic hair development/Pubarche: There was an inconsistent association between maternal GDM and pubarche in girls based on the four primary articles that studied this association. Age at peak height velocity: Hockett et al (27) examined the association between maternal GDM and pubertal timing in the daughters as reflected by growth parameters including peak height velocity (PHV) and age at PHV (APHV). APHV was 10.85 years in girls born to mothers with GDM and 11.12 years in girls born to mothers without GDM, with overlapping confidence intervals ( Table 2).…”
Section: Association Between Maternal Gestational Diabetes and Pubertmentioning
confidence: 99%